The Existence of Non-Muslim Minorities in Aceh Indonesia: A Study of Civil and Police Institutions - Mustaqilla, Safira; Abdullah, Irwan; Ichwan, Moch. Nur; Lailatussaadah, Lailatussaadah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
The implementation of Islamic law in Aceh had impact for the existence of non-Muslim minority groups. Even though they are guaranteed freedom to worship, harmony and protected, and can live side by side with the Aceh society, on the other hand, they are also feeling the impact of sharia. These implications are experienced by Christian women, not only among civil groups, but also police institutions. This article aims to complement the shortcomings of previous research, by mapping the relationships that existed between Muslim and non-Muslim groups in Aceh during the implementation of Islamic sharia. The research question is, how do these implications occur and why public space is limited for them. This research was conducted in Banda Aceh involving six informants and some were women, civil society groups and several police institutions, namely three Christian policewomen, through in-depth interviews and using several references related to the research subject. The results of the study indicated that, first, there are social spaces that have an impact on non-Muslim groups because they live in areas of Islamic sharia that require them to receive these regulations, such as the obligation to wear the veil for students, teachers and policewomen in police agencies. Then, there are limited facilities for worship, including for policewomen to provide spiritual guidance. Apart from that, there is little access to public space in government, which occurs among non-Muslim minority children who would like to develop their talents, as well as employees and in police agencies who could not develop their careers perfectly. This happens because they cannot have opportunities like the people of Aceh who are the